Rotating Disk Electrode Study of Carbon Supported Pt-Nanoparticles Synthesized Using Microwave-Assisted Method. (24th August 2017) - Vaarmets, Kersti; Valk, Peeter; Nerut, Jaak; Tallo, Indrek; Aruväli, Jaan; Sepp, Silver; Lust, Enn
Abstract : Carbon supported platinum catalysts are widely used in polymer electrolyte membrane fuel cell applications. In this study, the microwave-assisted synthesis method was used to analyze the effect of the Pt-nanoparticle size and content (mass %) on the electrochemical activity of oxygen electroreduction reaction. The Pt-nanoparticles were deposited using the microwave-assisted method onto the commercial Vulcan XC72, Vulcan XC72 activated with HNO3, or onto molybdenum carbide derived carbon – C(Mo2 C)750 °C. Variation of the pH of the reaction media influenced the Pt-nanoparticle size and Pt content in the catalysts prepared. The X-ray diffraction and low temperature nitrogen sorption methods were used to characterize the catalyst materials. The materials were electrochemically characterized using the rotating disk electrode technique in 0.1 M HClO4 solution. The catalytic activity of the catalyst depends strongly on the size and size distribution of the Pt-nanoparticles deposited onto the porous carbon support.